Intergenerational residential school attendance and increased substance use among First Nation adults living off-reserve: An analysis of the aboriginal peoples survey 2017 - Toombs, Elaine; Lund, Jessie I.; Mushquash, Aislin R.; Mushquash, Christopher J. (Frontiers in Public Health, 2023)
Introduction The Truth and Reconciliation Commission of Canada (TRCC) published 94 Calls to Action in 2015 to address long-term, intergenerational effects of the residential school system, highlighting the pervasive impact of colonialism on the wellbeing of Indigenous peoples in Canada. Indeed, research with Indigenous populations in Canada has captured that prior experiences of residential schools contributes to the intergenerational transmission of mental and physical health disparities. Despite these studies, further research is needed that contextualizes the influence of residential schools within broader frameworks that consider Indigenous social determinants of health in Canada. As such, the purpose of the present study was to examine patterns of substance use and mental and physical health among individuals with a history of residential school attendance (RSA) and individuals reporting parent or two-generation (parent and grandparent) RSA. Method Data from the Aboriginal Peoples Survey (2017), involving 10,030 First Nations individuals living off reserve, were analyzed. Results Self-reported mental and physical health scores were significantly lower among those had attended residential schools, whose parents attended residential schools, and whose grandparents attended residential schools, when compared to those who did not. Further, family RSA was associated with increased substance use among participants, though the findings were variable based on sex and specific substance analyzed. Meanwhile, individual and family RSA was not associated with increased likelihood of a mental health diagnosis. Discussion These findings provide additional support for how both parental and two-generation family histories of RSA are associated with individual physical and mental health outcomes. Further, these findings articulate the need for the TRCC's Calls to Action to be actually implemented, including community-based approaches that harness the strength of Indigenous people and communities who aim to close the gap in these health disparities for their children and families.